ANALYSIS OF STUDENTS' DIFFICULTIES IN SOLVING MATRIX PROBLEMS - Suci Wahyuni Sari; Sefna Rismen; Mulia Suryani (Media Inovasi Pendidikan dan Publikasi, 2023)
This study aims to determine the types of difficulties experienced by students in solving matrix questions in class XI TBSM students at SMK Negeri 3 Solok Selatan. This type of research is descriptive research with a qualitative approach. The research subjects were students of class XI TBSM SMK Negeri 3 Solok Selatan, odd semester of the 2022/2023 academic year. The research subjects consisted of 7 students. Data collection was carried out using test techniques and interview guidelines. The tests given are in the form of essay tests and structured interviews. The data analysis technique used is descriptive qualitative using the Miles and Huberman model. The results of the study show that difficulties in using concepts are seen when students are not yet able to remember, state and present a concept; difficulties in using principles are seen when students are not yet able to perform operational or algebraic calculations correctly; Difficulties in solving verbal problems can be seen when students have difficulty understanding word problems and are not able or precise in translating questions into mathematical form. These findings indicate the need for teachers to prepare suitable learning strategies to overcome student learning difficulties in solving matrix problems.